SOVEREIGNTY, GLOBAL NORMS AND SECURITY COOPERATION IN SOUTHEAST ASIA - Caleb Slayton (JWP (Jurnal Wacana Politik), 2018)
Discussions on cooperative security strategies in Southeast Asia often mention potential threats such as piracy,illegal fishing, terrorism, island disputes and even the security concerns posed by natural disasters. Theaforementioned threats are mutual, between not only the ten ASEAN countries but also neighbors, such asAustralia and Timor Leste, along with rising and global powers such as China and the United States. However,developing security cooperation even against mutual threats is hindered not only by geographic and monetaryrestraints but by differences in national ideology, national interests, differing historical perspectives, divergentlegal opinions as well as intentional and unintentional misinformation. Using the perspective of a multi-disciplineapproach to international relations realism and the security dilemma along with highlighting the sources ofmiscommunication that hinder long-term security cooperation, this paper argues that Indonesia and the UShave incorrect and sometimes dangerous perceptions of the other. Differing concepts on national sovereignty,interpretations of international law and the degradation of the rules-based order are all easily manipulated tofuel dangerous misperceptions. Cooperation and sovereignty seem more at odds than ever before. But militarycooperation can still be successful using honest assessments that avoid false information and instead pursuesincere engagements.